Sistema regional de monitoramento de seca. - PEDROSA, João Paulo da Costa (Universidade Federal do Pará, 2019)
Drought is a natural phenomenon of meteorological origin, due to a precipitation deficit, which is verified every year in different regions of the globe, being therefore a recurring feature of the climate and not a rare occurrence. A drought situation can result in a natural disaster if there is no local resilience as a capacity for managing water resources to minimize their adverse effects. In many regions, as in developing countries, the consequences of droughts reach such a magnitude that they are often classified as catastrophic, causing famine, deaths and population exoduses. Considering this problem, the present study adapted a physical-mathematical model for the local conditions able to monitor drought based on the Palmer Drought Severity Index (ISSP) through changes in latitude, field capacity, water balance of Thornthwaite and the data of the files needed to calculate the index. The model used precipitation and air temperature data from 1987 to 2014. The model also had to be compiled for the C ++ language. We obtained as an answer an index with better reliability by the fact of using data with high resolution and more representative for the Amazon region.